2019
DOI: 10.15296/ijwhr.2019.57
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Risk Factors Associated With Infertility

Abstract: Objectives: Infertility is one of the important complications in gynecology and the aim of the present study was to investigate the etiology and risk factors associated with infertility in the southern region of Iran. Materials and Methods: This cross-sectional study was conducted in infertility centers of Hormozgan University of Medical Science (HUMS). Totally, 250 infertile couples were included. The variables including socio-demographic characteristics, smoking, body mass index (BMI), and infertility statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 28 publications
6
36
0
2
Order By: Relevance
“…In PCOS, levels of hormones including androgens and testosterone increase due to high levels of luteinizing hormone (LH) and low levels of the follicular-stimulating hormone (FSH), so follicles in these individuals are prevented from producing a mature egg. Furthermore, PCOS increases the risk of insulin resistance, along with type 2 diabetes, which is one of the causes of infertility [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In PCOS, levels of hormones including androgens and testosterone increase due to high levels of luteinizing hormone (LH) and low levels of the follicular-stimulating hormone (FSH), so follicles in these individuals are prevented from producing a mature egg. Furthermore, PCOS increases the risk of insulin resistance, along with type 2 diabetes, which is one of the causes of infertility [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the underlying causes of primary infertility have been suggested to include environmental toxins, smoking, obesity, and psychological stress [ 7 , 8 ]. In addition, sociodemographic factors like age, race, education level, marital age, type of family, employment and socioeconomic status have been also evaluated for causal relationship [ 9 , 10 ]. Physical activity, as an essential lifestyle modification component, has been thoroughly investigated against female infertility, but controversial research suggestions were concluded in this regard [ 11 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The WHO defines infertility as a disease characterized by the failure to establish a clinical pregnancy after 12 months of regular, unprotected sexual intercourse or due to an impairment of a person's capacity to reproduce either as an individual or with his or her partner [1]. The prevalence of infertility has increased significantly in recent years; its global prevalence is reported to be 10%-15% [2].…”
Section: Introductionmentioning
confidence: 99%